Optimalisasi Peran Mahasiswa KKN SISDAMAS dalam Peningkatan Pendidikan Desa: Studi Participatory Action Research - Muhammad Fanza Maulana (Sarau Institute, 2026)
This study aims to analyze the optimization of the role of students in the SISDAMAS-based Community Service Program (KKN) as teaching facilitators in improving education in Tanggulun Village through a Participatory Action Research (PAR) approach. The study employed a descriptive qualitative method by integrating PAR and SISDAMAS frameworks. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing, supported by semi-quantitative indicators and validated through source and method triangulation. The findings indicate that all stages of the program, including socialization, social mapping, participatory planning, and implementation at kindergarten, elementary, and junior high school levels, were carried out in a participatory and collaborative manner. Educational activities such as storytelling programs, literacy sessions, and youth workshops contributed to increased student engagement, more interactive learning environments, and strengthened social values. These findings demonstrate that the integration of SISDAMAS and PAR is effective in optimizing the role of students as teaching facilitators while promoting community-based educational empowerment. This study implies that the integration of SISDAMAS and PAR can serve as an alternative strategy for sustainable educational development in rural areas.